Enhancing rural students’ perceived relevance and career interest in engineering through 3D printing - Tang, Hengtao; Qian, Yingxiao (Frontiers in Education, 2025)
IntroductionEngineering education has the potential to create meaningful career pathways for rural students by empowering them to address local challenges and contribute to their communities. However, rural students remain underrepresented in engineering, often due to a perceived disconnect between traditional curricula and their lived experiences. To bridge this gap, integrating 3D printing to connect learning with local context may be a viable solution.MethodsThis convergent mixed methods study examined the impact of engaging in 3D printing practices on rural students’ perceived relevance of engineering and their interest in pursuing engineering careers. The study engaged students in hands-on making practices that reflected their personal and community contexts. Quantitative data (e.g., surveys) and qualitative data (e.g., semi-structured interviews) were collected and analyzed separately and then integrated to provide a comprehensive finding.ResultsQuantitative results showed significant increases in students’ perceived authenticity and career interests after engaging in 3D printing sessions. Qualitative findings extended and explained quantitative results by discussing how 3D printing connected learning to students’ lived experience and career aspirations. The integrated findings underscored the potential of 3D printing for supporting rural students’ perceived relevance to learning and career interests in engineering.DiscussionThis study demonstrated that 3D printing allowed students to engage in making practices closely relevant to their experience and community. When students recognize the relevance, they tend to engage in engineering and align it with their career aspirations. The findings underscore the importance of providing contextually meaningful learning experiences to support rural students’ participation in STEM and foster interest in STEM careers.